Clinical Outcomes of Concomitant Use of Proton Pump Inhibitors and Dual Antiplatelet Therapy: A Systematic Review and Meta-Analysis - Guo, Hongzhou; Ye, Zhishuai; Huang, Rongchong (Frontiers in Pharmacology, 2021)
Background: The safety and efficacy associated with the use of proton pump inhibitors (PPIs) by patients with coronary artery disease receiving dual antiplatelet therapy (DAPT) remain unclear. Methods: The evaluated outcomes included combined major adverse cardiovascular events (MACEs), myocardial infarction (MI), all-cause mortality, and gastrointestinal (GI) bleeding. A random effects meta-analysis, stratified by study design, was performed and heterogeneity was assessed using the I2 statistic. Results: In total, 22 studies of 190,476 patients were included. Analysis of RCTs showed that there were no significant differences in the incidences of MACEs (risk ratio [RR] = 0.89 [95% confidence interval (CI) = 0.75–1.05]), MI (RR = 0.93 [95% CI = 0.76–1.15]), and all-cause mortality (RR = 0.79 [95% CI = 0.50–1.23]) in the PPI groups vs. the non-PPI groups. Pooled data from observational studies revealed an inconsistent association between the use of each PPI subtype and the increased risks of MACEs during clopidogrel treatment. There was no increased risk of MACEs or all-cause mortality associated with the use of PPIs (as a class) and other P2Y12 inhibitors. Both the RCTs and observational studies revealed that the use of PPIs significantly reduced the risks of GI bleeding. Conclusions: The use of PPIs was associated with a reduced risk of GI bleeding in patients treated with DAPT after percutaneous coronary intervention or acute coronary syndrome. There was no clear evidence of an association between the use of PPIs and adverse cardiovascular events.